Biosimilar knowledge and viewpoints among Brazilian inflammatory bowel disease patients - Garcia, Karoline Soares (2021)
Background: In this analysis we aimed to describe Brazilian inflammatory bowel disease (IBD) patients’ knowledge and perceptions regarding biosimilars and compare with viewpoints from non-Brazilian patients. Methods: An online survey consisting of 19 questions was made available by the European Federation of Crohn’s and Ulcerative Colitis Associations between July 2018 and December 2018. Only respondents who had heard of biosimilars were asked to respond to all of the questions. Results: A total of 102 Brazilian IBD patients responded to the survey. The majority (78.4%) of patients had been exposed to anti-tumor-necrosis-factor drugs and 63.4% of them had heard of biosimilars. Brazilian respondents worried significantly more about biosimilars being less effective than the originator (62.5% versus 47.9%, p value 0.03) and molecular differences between biosimilars and originators (53.1% versus 31.8, p value 0.001) as compared with non-Brazilian IBD patients. The majority of Brazilian (75%) and non-Brazilian (64.1%) respondents thought that the lower cost of biosimilars should not come before their safety and efficacy (p value 0.09). In addition, 79.1% of Brazilian respondents believed that the arrival of biosimilars will have an impact on the management of IBD. Conclusions: Brazilian patients reported higher rates of misconceptions regarding biosimilars than non-Brazilian IBD patients. Although patients still worry about different aspects regarding biosimilars, they also tend to be confident that biosimilars will have an impact on the management of their disease. With the recent approval of many biosimilars in Brazil and the imminent widespread use of these drugs, our data raise awareness for the need of providing patient education to prevent negative expectations toward switching to biosimilars.